2010
DOI: 10.1038/jhg.2010.94
|View full text |Cite
|
Sign up to set email alerts
|

Human endogenous retrovirus K14C drove genomic diversification of the Y chromosome during primate evolution

Abstract: The male-specific region of Y chromosome (MSY) has accumulated a higher density of human endogenous retroviruses (HERVs) and related sequences when compared with other regions of the human genome. Here, we focused on one HERV family, HERV-K14C that seemed to integrate preferentially into the Y chromosome in humans. To identify every copies of HERV-K14C in the human genome, we applied computational screening to map precisely the locus of individual HERV-K14C copies. Interestingly, 29 of all 146 copies were loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…The impact of the HERV-K 14C on host genomic diversity is probably among the most elegant examples. By analyzing the multiple-copy element K14C in human and primate Y chromosome, the authors demonstrated that despite the integration being present in more ancient primate hosts, the duplication event happened no longer than 10 million years ago, indicating that this retroelement contributed to the genomic diversification of this chromosome during speciation of particular primate lineages ( 25 ).…”
Section: Background On Human Endogenous Retrovirusesmentioning
confidence: 99%
“…The impact of the HERV-K 14C on host genomic diversity is probably among the most elegant examples. By analyzing the multiple-copy element K14C in human and primate Y chromosome, the authors demonstrated that despite the integration being present in more ancient primate hosts, the duplication event happened no longer than 10 million years ago, indicating that this retroelement contributed to the genomic diversification of this chromosome during speciation of particular primate lineages ( 25 ).…”
Section: Background On Human Endogenous Retrovirusesmentioning
confidence: 99%
“…Several ERVs are located on the male Y chromosomes of human and NHPs (360,638,639), providing evidence of their transmission through the male gametes in these species. Specific characteristics of the Y chromosome, such as reduced recombination and low number of functional genes, may have prevented the loss of integrated sequences and allowed integration with no deleterious effect (360), thus favoring viral endogenization.…”
Section: Male Germ Line Infectionmentioning
confidence: 99%
“…Endogenous retroviruses are preferentially located on the Y chromosomes of human, chimpanzee and orang-utan ( Sin et al, 2010 ). It has been suggested that reduced recombination of the Y chromosome renders loss of integrated sequences less likely.…”
Section: Endogenous Viral Elements (Eve)mentioning
confidence: 99%